Reproduction in the Impala (Aepyceros melampus Lichtenstein), with particular reference to the population in Mkuzi Game Reserve, Zululand - Bothma, K. (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1972.